2017
DOI: 10.3389/fpubh.2017.00243
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on the Existing Screening Pathways for Lynch Syndrome Identification

Abstract: BackgroundLynch syndrome (LS) is the most common hereditary colon cancer syndrome, accounting for 3–5% of colorectal cancer (CRC) cases, and it is associated with the development of other cancers. Early detection of individuals with LS is relevant, since they can take advantage of life-saving intensive care surveillance. The debate regarding the best screening policy, however, is far from being concluded. This prompted us to conduct a systematic review of the existing screening pathways for LS.MethodsWe perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Although MSI is sensitive for Lynch syndrome cancers, it is not specific, as 15%–20% of sporadic colon cancers have MSI 12 13. Loss of protein expression for any of the MMR proteins indicates a genetic defect, but it does not differentiate among germline, somatic or epigenetic sources 12. Approximately 15% of sporadic MSI CRC is found to be caused by acquired somatic CpG methylation of the MLH1 gene promotor rather than germline mutations in the aforementioned MMR genes, as seen in Lynch syndrome 10 12 13.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although MSI is sensitive for Lynch syndrome cancers, it is not specific, as 15%–20% of sporadic colon cancers have MSI 12 13. Loss of protein expression for any of the MMR proteins indicates a genetic defect, but it does not differentiate among germline, somatic or epigenetic sources 12. Approximately 15% of sporadic MSI CRC is found to be caused by acquired somatic CpG methylation of the MLH1 gene promotor rather than germline mutations in the aforementioned MMR genes, as seen in Lynch syndrome 10 12 13.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the association of the defective MMR (dMMR) genes and colon cancer in patients with Lynch syndrome, the National Institute for Health and Care Excellence in 2017 confirmed a universal screening approach for patients with newly diagnosed CRC to undergo either MSI DNA-based testing or immunohistochemistry analysis of their tumours to guide further follow-up testing for Lynch syndrome 12 13. Early identification of Lynch syndrome may reduce further cancer risk through intensive screening, follow-up programmes or prophylactic surgery 12. Recent guidelines from the American Society of Clinical Oncology recommend dMMR screening in patients with CRC, as establishing a diagnosis of Lynch syndrome and subsequent active management of cancer risk has been demonstrated to benefit gene mutation carriers; even more so, the diagnosis creates prevention opportunities in all at-risk relatives 13.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported a large heterogeneity of clinical paths to detect LS patients across Europe [17]. In Italy, although international guidelines favour the universal screening approach [15,16], there is no organized screening pathway in place aimed to identifying individuals with LS [18].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, LS screening protocols are more likely in research and academic centers, and less likely in community hospitals . A recent systematic review of existing screening pathways for LS revealed only five sites with structured and permanent screening protocols: three in the US, one in Australia, and one in Europe. Of these, three followed a universal screening approach including all patients with CRC.…”
Section: Introductionmentioning
confidence: 99%